2022
DOI: 10.1159/000522482
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate: A Safe Nutrient, Not Just a Simple Additive

Abstract: Background: In 2017, an European Food Safety Authority (EFSA) opinion on the use of glutamate and its salts as food additives led to an ADI of 30mg/kg body weight/day. Then, in 2021, an EFSA statement presented a proposal for harmonising the establishment of Health-Based Guidance Values for nutrients that are also regulated substances (including food additives). The present review argues that the 2017 glutamate ADI is unsuitable because safety of glutamate should firstly consider its status as a nutrient and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Intriguingly, the most abundant amino acids in the high-energy breakfast were leucine, glutamic acid and proline, indicating that the amino acid postprandial response cannot entirely be explained by the abundance of the amino acids eaten. Further, glutamic acid is one of the most abundant amino acids found in dietary protein (28) , but in the present study, we observed only small changes in glutamic acid after the meal compared with most other amino acids, which has also been observed by others (29) . It has been suggested that glutamic acid is metabolised to various amino acids in the enterocyte, mainly alanine but also proline (28) , which may explain the observations in the present study.…”
Section: Potential Mechanisms and Comparison With Other Studiessupporting
confidence: 78%
“…Intriguingly, the most abundant amino acids in the high-energy breakfast were leucine, glutamic acid and proline, indicating that the amino acid postprandial response cannot entirely be explained by the abundance of the amino acids eaten. Further, glutamic acid is one of the most abundant amino acids found in dietary protein (28) , but in the present study, we observed only small changes in glutamic acid after the meal compared with most other amino acids, which has also been observed by others (29) . It has been suggested that glutamic acid is metabolised to various amino acids in the enterocyte, mainly alanine but also proline (28) , which may explain the observations in the present study.…”
Section: Potential Mechanisms and Comparison With Other Studiessupporting
confidence: 78%
“…This results in ATP synthesis and elevated mitochondrial ATP levels. 21,22 Additionally, the studies by Carole 16,23 demonstrated that HA derivatives, such as amino acid derivatives, can effectively decelerate HA degradation. This allows HA to persist in the extracellular matrix and sustain receptor binding for an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, CD44 is involved in cellular uptake of hyaluronan, promoting endocytosis of HA‐Glu into the cell plasma. The internalized HA‐Glu is cleaved by hydrolases within the cell cytoplasm, resulting in the release of glutamate that subsequently generates glutathione (GSH) to maintain redox balance and alleviate oxidative stress 21 . Hydrolases may also cleave the grafting glutamate site into glutamine, which then migrates into the mitochondria to perform its function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these concerns were invalidated, as numerous studies reporting adverse health effects used a parenteral administration route and/or relied on doses far exceeding the typical levels consumed in food products. Current reports on its dietary consumption do not seem to raise safety concerns [24,25].…”
Section: Glutamate and Dietary Interventionmentioning
confidence: 99%